Process-Based Instruction and Paragraph Writing Performance in Ethiopian High Schools - Gebre, Kifle Desalegn; Anshu, Alemu Hailu (JELITA, 2026)
This study aimed to examine students’ attitudes toward the effectiveness of process-based instruction in improving their paragraph writing skills. The study sought to determine the impact of the instruction on skill enhancement and students’ perceptions of its implementation. A quasi-experimental design was applied, as it was suitable for two intact classes to determine cause-effect relationship. From ten sections of grade ten, two were purposively selected: section 01 was randomly assigned to the experimental group and section 02 to the control group. A mixed-methods enhanced validity and reliability, including tests, questionnaires, and interviews. Tests assessed paragraph writing performance, while questionnaires with 40 students and interviews with 6 examined effectiveness. Quantitative data were analyzed using a t-test and descriptive statistics, and qualitative data thematically. Findings revealed that the experimental group outperformed control group, with statistical significance (t (39) = -3.750., p < .000) and a moderate effect size (Cohen’s d = 0.84). Process-based instruction also enhanced students’ interest in writing, encouraged feedback exchange, and promoted collaborative writing. The study improved students’ paragraph writing performance by emphasizing recurring practices, creativity, and peer-feedback. The study guided teachers to structure instructional phases, integrate related language skills, and apply continuous formative assessments, fostering social interaction, and gradual learning progress.